DESCRIPTION OF THE PROCESSES OF ORGANIZING THE ACTIVITIES OF THE STANDARDIZATION DEPARTMENT IN THE ORGANIZATION (American Journal of Technology and Applied Sciences, 2024)
The organization's standardization system, standardization processes, management of the standardization service using theMarkov chain, and the procedure for developing standards within the organization.